Diabetes and kidney dysfunction markedly alter the content of sphingolipids carried by circulating lipoproteins - Hammad, Samar M; Hunt, Kelly J; Baker, Nathaniel L; Klein, Richard L; Lopes-Virella, Maria F (Journal of clinical lipidology, 2022)
•Assessing sphingolipid distribution in plasma lipoproteins is clinically valuable.•Plasma levels do not consistently reflect changes in circulating lipoproteins.•HDL sphingolipids are significantly lower in diabetes than in controls.•LDL sphingomyelins are higher in patients with diabetes and macroalbuminuria. We have previously shown that very long ceramides/lactosylceramides predicted the development of macroalbuminuria (MA) in type 1 diabetes and expanded our studies into type 2 diabetes. This study proposes comparing the levels of plasma sphingolipids and their distribution in circulating lipoproteins (VLDL/IDL, LDL, HDL2 and HDL3) between a healthy control group and two groups of subjects with type 2 diabetes, one with and other without MA. Plasma and lipoprotein sphingolipids/glycosphingolipids were measured using HPLC-MS/MS in 114 subjects (40 controls; 74 type 2 diabetes, 40 without MA; and 34 with MA) and the levels were compared between controls and the two groups of diabetes. Group effect sizes were calculated using Cohen's d. Sphingomyelin species carried by LDL are significantly higher in diabetic patients with MA than in those with normal albumin excretion rate (AER). Compared to controls, significant decreases in the levels of sphingolipids carried by HDL in patients with diabetes with normal AER or MA were observed for all sphingolipid classes except for hexosylceramide, which was normal in diabetic patients without MA. Although lower than in controls, the levels of lactosylceramides carried by HDL2/HDL3 were significantly higher in diabetes with MA. Considering the critical role sphingolipids play in major cell biological responses and cell signaling pathways, the consequences for disease development of changes in the distribution of sphingolipids/glycosphingolipids carried by lipoproteins could be considerable. Our work is just a first step to address a considerable gap in our present knowledge in this important field.